AUGMENTED AND VIRTUAL REALITY IN THE MEDIA: QUESTIONING THE CONCEPT OF “IMMERSIVE” JOURNALISM - Krstić, Aleksandra R. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
This article questions and analyzes the concept of “immersive” journalism, which has emerged from advanced technologies of augmented and virtual reality and which has already been changing the role of the media, journalism and audiences’ experiences. Developed and applied in media and tech companies in the Western countries, this form of journalism represents one of the growing business models used by companies oriented towards improving and developing social networks, mobile platforms and multimedia online portals. Immersion of the audience into journalistic stories, which are upgraded by AR and VR technologies, represents the key change of our understanding, analyzing and representing the reality, and at the same time brings into question ethical and professional journalistic standards. Built on the growing body of academic scholarship and contemporary research in the field, this article critically examines the concept “immersive” journalism and looks into relevant aspects of its theoretical foundations and practical implementation in the media industry and the university education of journalists.